2014
DOI: 10.1007/s12272-013-0319-8
|View full text |Cite
|
Sign up to set email alerts
|

Co-culture with NK-92MI cells enhanced the anti-cancer effect of bee venom on NSCLC cells by inactivation of NF-κB

Abstract: In the present study we experimented on a multimodal therapeutic approach, such as combining chemotherapy agent (Bee venom) with cellular (NK-92MI) immunotherapy. Previously bee venom has been found to show anti-cancer effect in various cancer cell lines. In lung cancer cells bee venom showed an IC(50) value of 3 μg/ml in both cell lines. The co-culture of NK-92MI cell lines with lung cancer cells also show a decrease in viability upto 50 % at 48 h time point. Hence we used bee venom treated NK-92MI cells to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Further, the DNA binding activity and luciferase activity of NF-κB was also inhibited after co-culture with BV treated NK-92MI cell lines. The knock down of death receptors with siRNA was observed to reverse the decrease in cell viability and NF-κB activity after co-culture with BV treated NK-92MI cells [50]. Similar effects of death receptor mediated BV activity was observed by Jo et al [41], where they suggested that BV and MEL induces apoptotic cell death in SKOV3 and PA-1 ovarian cancer cells through induction of death receptors and inhibition of JAK2/STAT3 pathway.…”
Section: Anticancer Effects Of Bv and Its-conjugatesmentioning
confidence: 65%
“…Further, the DNA binding activity and luciferase activity of NF-κB was also inhibited after co-culture with BV treated NK-92MI cell lines. The knock down of death receptors with siRNA was observed to reverse the decrease in cell viability and NF-κB activity after co-culture with BV treated NK-92MI cells [50]. Similar effects of death receptor mediated BV activity was observed by Jo et al [41], where they suggested that BV and MEL induces apoptotic cell death in SKOV3 and PA-1 ovarian cancer cells through induction of death receptors and inhibition of JAK2/STAT3 pathway.…”
Section: Anticancer Effects Of Bv and Its-conjugatesmentioning
confidence: 65%
“…Apoptosis occurs through two mechanisms that are expressed in the mitochondria 35) and from the cell surface 30) . In the cell surface, receptors such as perform a major role in resistance to various treatment applied [36][37][38] . In other words, the regulation of NF-κ B can be a key to the treatment in the cancer cells.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…In korean medicine, the studies of herb medication and pharmacopuncture for inducing apoptosis have been actively conducted 13,[16][17][18] , and lately, there are many studies that BV has the effect of regulation of NF-κ B 24,[26][27][28][29][30][31]35,38,39) .…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…BV induces apoptotic cell death through several cancer cell death mechanisms, among them the activation of PLA2 by melittin is the critical mechanism for the anti-cancer activity of BV. The conjugation of cell lytic peptide (melittin) with hormone receptors and gene therapy carrying melittin can be useful as a novel targeted therapy for some types of cancer (Orsolic, 2012;Kollipara et al, 2014).…”
Section: Antitumor Activity Of Bee Venommentioning
confidence: 99%